Respons Pertumbuhan Dan Produksi Kedelai (Glycine max (L.) Meriil) Terhadap Konsentrasi Dan Cara Pemberian Pupuk Organik Cair - Mestika Amelia Sinuraya; Asil Barus; Yaya Hasanah (Universitas Sumatera Utara, 2016)
Low production of soybean caused by reduction of arable land due inorganic fertilizer contionously. Therefore, it should be done improvements by used liquid organic fertilizer. This research was conducted in Desa Tanjung Anom, Medan with altitude ± 25 meters above sea surface began on September to November 2015. This research used factorial randomized block design with two factors. The first factor was concentration liquid organic fertilizer (20; 40; 60 and 80 ml/L water) and the second factor was application methods liquid organic fertilizer with (spray and flush). Variable observed was total leaf area, shoot dry weight, root dry weight, dry weight of seeds per plant, dry weight of 100 seeds. The result of this research showed that concentration of liquid organic fertilizer of 40 ml increased the yield of soybean production in almost all the variable observation. Application methods of liquid organic fertilizer by flushed increased the yield of soybean production in almost all the variable observation. Interaction of concentration and application method of liquid organic fertilizer increased the yield of soybean production with the best treatment combination in concentration of 40 ml and by flushed. Key words: soybean, liquid organic fertilizer, concentration, application methods